Histomorphological features and IHC expression in endometrial and endocervical adenocarcinoma - Ann Maria Sunny; Saji Mary Varghese; Letha V; Sankar S (Asian Journal of Medical Sciences, 2023)
Background: The distinction of endometrial adenocarcinoma (EMA) from endocervical adenocarcinoma (ECA) has great significance preoperatively, since the therapeutic plan depends on the primary site of tumor. Immunohistochemistry (IHC) is an ancillary method in distinguishing primary EMA and ECA, especially in cases of histomorphological overlap. Aims and Objectives: Primary objective of this study was to describe the expression of IHC markers–estrogen receptor (ER), vimentin, monoclonal carcinoembryonic antigen (CEA), P16 in EMA and ECA. Secondary objective of this study was to describe the histomorphological features of EMA and ECA. Materials and Methods: This is a descriptive study done at the Department of Pathology, Government Medical College, Kottayam between November 2019 and May 2021. The sample size was 54 which included primary adenocarcinoma diagnosed on curettage biopsies. IHC was performed using ER, Vimentin, P16, and mCEA. A semiquantitative scoring was done using the German IHC scoring system. Results: Histomorphological features and IHC expression in EMA and ECA were studied. Percentage of cases with expression of IHC markers is as follows. In endometrioid EMA-ER in 100% of cases, Vimentin 83.3%, P16 0%, and CEA in 7.3% cases. About 80% of serous carcinomas showed P16 and vimentin positivity with negative staining for ER and CEA. In ECA-ER in 0% cases, vimentin 16.7%, P16 80%, and CEA in 66.7% of cases. Based on histomorphologic appearance, the common histologic subtype of EMA was endometrioid EMA followed by serous carcinoma. In ECA, the usual type was more common than gastric type. Conclusion: IHC markers-ER, vimentin, P16, and CEA are useful in distinguishing endometrioid EMA and ECA.